Congenital deafness and vestibular disorders: a systematic literature review - Genovese, Elisabetta; Segato, Erika; Liberale, Carlotta; Zampieri, Erica; Monzani, Daniele; Apa, Enrico; Palma, Silvia; Nocini, Riccardo (Frontiers in Neurology, 2024)
Introduction Congenital deafness is a pathological entity that represents an economical and social burden, affecting up to 0.2% of newborns in Europe. Sensorineural hearing loss (SHL) is caused by a variety of factors, including congenital abnormalities, perinatal infectious diseases and genetic syndromes. The inner ear’s vestibular system, nestled alongside the auditory organs, is crucial for balance maintenance. Its close connection with the auditory system means that disturbances in one often coincide with disturbances in the other, highlighting their intertwined functions. With this review we aim to describe objective vestibular tests found in literature and to study their use for diagnosis of vestibular disturbances in patients affected by congenital deafness. Methods The review is conducted with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 guidelines. The search string used was: [(congenital deafness) OR (congenital hearing loss) OR (congenital hypoacusia)] AND [(vestibular disorders) OR (vertigo)]. An initial abstract reading selection was made, and a subsequent comprehensive full-text reading. For each article, we identified the type of vestibular test utilized and its corresponding outcome. Results Out of the initial—papers identified through the search string—articles met the eligibility criteria for further analysis through abstract and full-text reading. After further selection—articles were chosen for detailed examination, focusing on the data of patients. Conclusion Congenital hearing loss profoundly affects a child’s development, especially in language and communication skills, and it is frequently associated with a pathological vestibular system. Early identification allows timely intervention with personalized therapies. In current literature, there is still no gold standard test to identify balance disorders in patients with congenital hearing loss. There is considerable variability on the subject due to the inclusion of diverse patients with various diagnoses, alongside a wide range of available technologies. Managing such conditions necessitates collaboration among healthcare providers, ensuring comprehensive care through prompt diagnosis and personalized treatment plans. Ongoing research aims to further improve screening methods and develop precision medicine approaches tailored to individual needs.